ANALISIS FAKTOR RISIKO CARPAL TUNNEL SYNDROME PADA OPERATOR JAHIT BAGIAN PRODUKSI PT LEADING GARMENT - Arya Yudistira; Suroto Suroto; Siswi Jayanti (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2022)
Carpal Tunnel Syndrome (CTS) is one of the occupational diseases around the wrist caused by compression of the median nerve which is limited to the carpal bones and also the transverse carpal ligament. Symptoms of CTS will often appear and can interfere with work productivity. This study aims to determine the relationship of risk factors of age, nutritional status, repetitive movements and work postures with CTS on sewing operator PT Leading Garment. The type of research used is quantitative explanatory research with a cross sectional approach. The population used is sewing operator PT Leading Garment as many as 60 operators with a sample of 47 operators using simple random sampling. Data were collected by using the Phalen test and a questionnaire to determine the presence of CTS, age through a questionnaire, nutritional status through BMI results, and through observation to determine the repetitive movements and work postures of the operator. The results showed that as many as 66.0% of sewing operators were positive for CTS. Based on the results of the Chi Square test, it was found that there was a statistically significant relationship between repetitive movements (p=0.027) and work posture (p=0.030) with CTS. While the variables of age (p=0.465) and nutritional status (p=156) did not have a significant relationship with CTS. The conclusion is that there is a significant relationship between repetitive movements and work posture with CTS and there is no significant relationship between age and nutritional status with CTS on PT Leading Garment sewing operators.